2020
DOI: 10.1093/nar/gkaa1108
|View full text |Cite
|
Sign up to set email alerts
|

PDCD2 functions as an evolutionarily conserved chaperone dedicated for the 40S ribosomal protein uS5 (RPS2)

Abstract: PDCD2 is an evolutionarily conserved protein with previously characterized homologs in Drosophila (zfrp8) and budding yeast (Tsr4). Although mammalian PDCD2 is essential for cell proliferation and embryonic development, the function of PDCD2 that underlies its fundamental cellular role has remained unclear. Here, we used quantitative proteomics approaches to define the protein-protein interaction network of human PDCD2. Our data revealed that PDCD2 specifically interacts with the 40S ribosomal protein uS5 (RPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 59 publications
(89 reference statements)
4
33
0
1
Order By: Relevance
“…Purification of Enp1-FTP particles from cells in which Tsr4-AID was depleted for two hours revealed that both Rrp12 and Bud23 accumulated in the absence of Tsr4 (Figure S5D). Because Tsr4 facilitates Rps2 expression (Black et al 2019;Rössler et al 2019;Landry-Voyer et al 2020), this result further supports the notion that Rps2 is needed for the release of Bud23 from the pre-40S.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Purification of Enp1-FTP particles from cells in which Tsr4-AID was depleted for two hours revealed that both Rrp12 and Bud23 accumulated in the absence of Tsr4 (Figure S5D). Because Tsr4 facilitates Rps2 expression (Black et al 2019;Rössler et al 2019;Landry-Voyer et al 2020), this result further supports the notion that Rps2 is needed for the release of Bud23 from the pre-40S.…”
Section: Resultssupporting
confidence: 78%
“…Depletion of Tsr4, the chaperone of Rps2, also causes Bud23 to accumulate on pre-40S. We and others recently identified Tsr4 as an essential, dedicated chaperone that facilitates Rps2 expression (Black et al 2019;Rössler et al 2019;Landry-Voyer et al 2020). To further support the idea that Rps2 is needed for Bud23 release, we asked if Bud23 accumulates on pre-40S particles in Tsr4-depleted cells.…”
Section: Resultsmentioning
confidence: 93%
“…Purification of Enp1-FTP particles from cells in which Tsr4-AID was depleted for two hours revealed that both Rrp12 and Bud23 accumulated in the absence of Tsr4 (Figure S5D). Because Tsr4 promotes Rps2 expression (Black et al 2019;Rössler et al 2019;Landry-Voyer et al 2020), this result further supports the notion that Rps2 is needed for the release of Bud23 from the pre-40S.…”
Section: Depletion Of Tsr4 Also Causes Bud23 To Accumulate On Pre-40ssupporting
confidence: 78%
“…KEGG analysis showed the SRMS co-expression genes mainly enrichment in the ribosomal, proteasomal, oxidative phosphorylation, and DNA replication pathways. Ribosomes, comprised of ribonucleoprotein and non-coding ribosomal RNAs in eukaryotes, are conserved molecular structures required for protein synthesis [ 35 ]. Cancer development and progression are associated with ribosomal dysregulation, which affects the expression of key factors involved in tumorigenesis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%